Hubungan Antara Pengetahuan Haid Dengan Sikap Siswa Kelas V dan VI Sekolah Dasar Islam Terpadu (SDIT) Insan Madani Bongas Tahun 2024 - Khoirul Magfiroh; Anjar Sulistyani; Dewi Utami (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Knowledge refers to information or facts collected and resulted from people learning through sensory perception which lead and shape their action. It is necessary for students both male and female to understand menstruation knowledge. Although the boys do not have experience of having menstrual cycle, they need to understand in order to behave appropriately towards their female friends, such as showing respect, emphaty and support for their peers. The study aims to investigate the correlation between students’ mestruation knowledge towards their attitudes in grade fifth and sixth of Integrated Islamic Primary School of Insan Madani Bongas.The study uses quantitative approach to examine relationship between the knowledge and attitude. To collect data, the researcher distributes the questionnaires to students. To describe the correlation between the variables, for data analysis the researcher uses classical assumption test and simple linear regression. This study shows that the knowledge and attitudes of sixth-grade students towards menstruation are better than those of fifth-grade students. And, the knowledge and attitudes of female students regarding menstruation are better than those of male students since females have personal experience with menstruation, while males do not. Finally, in conclusion, there is a correlation between students’ menstruation knowledge and their attitudes in fifth and sixth grade of SDIT Insan Madani Bongas.